Effects of physical factors and synthetic media on mycelial growth of Lyophyllum decastes - S. Ohga, C.P. Pokhrel, R.K.P. Yadav (Journal of Ecobiotechnology, 2009)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold; mso-bidi-font-style: italic;">We investigated the effects of light, moisture, amino acids, vitamins and mineral nutrients on mycelial growth of the medicinal mushroom Lyophyllum decastes. Mycelial growth experiments were carried out on solid media. The best mycelial extension was recorded in total dark conditions, followed by 12 h alternating light/dark and total light, in respective order. This fungus grew well on substrate containing 65% moisture. Of the eight amino acids tested, the best growth (61.73 mm, after two-week incubation) was supported by glutamic acid, followed by proline and alanine. Six vitamin sources were used and riboflavin was the most utilizable (56.57mm). CaSO4 was found to be the most favorable mineral source for growth (67.80 mm).